Upaya Peningkatan Penerimaan Pajak Bumi dan Bangunan (PBB-P2) Pada BPKPAD Kabupaten Kepulauan Selayar - Musdalifa; Sari Den Ka, Veronika; Akrim, Djusdil (PT Bone Jaya Kreatif, 2023)
This study aims to determine the Efforts to Increase Home and Property Tax Revenues (PBB-P2) in the BPKPAD Selayar Islands Regency. This research method used Descriptive Qualitative by structured interviews with several respondents. They are staff of relevant agencies, tax collectors and taxpayers. The data is used in this study are answer in interviews, and secondary data which are the number of PBB-P2 receipts in 2016-2018. The results of the study indicate that the efforts made by BPKPAD of Selayar Islands Regency in increasing PBB-P2 revenues, namely 1). PBB-P2 tariff solving; 2). Outreach, give an appeal and issue Maturity, Arrears and Payment Fines PBB-P2; 3). Provide understanding to taxpayers before completing SPOP and LSPOP.